The two degree initiative for food and agriculture - Online stakeholder consultation (Day 1) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2020)
One-Health is a collaborative, multisectoral, and transdisciplinary approach – working at the local, regional, national, and global levels – with the goal of achieving optimal health outcomes recognizing the interconnection between people, animals, plants, and their shared environment. Pests, diseases and other biotic stresses are major threats to the health of crops, livestock, humans and ecosystems, now convoluted by the current coronavirus pandemic (COVID-19). Climate change will affect the distribution and dynamics of such pests and diseases. It will also disrupt complex interactions and tradeoffs between different ecosystems, with huge adverse economic implications. Our advanced Climate-informed One-Health approach builds on CGIAR’s track records in this area, framing the nexus of crop, livestock, human and ecosystem health, pest and disease epidemiology and control, food production, safety and nutrition, and climate change as a complex public health issue. We are working towards a field-grounded, conceptually refined response to the scale of this global challenge. The holistic One-Health approach enables our contributions to plant and soil health for improved agricultural productivity, resilience, and community livelihood.